Analysis of Factors Affecting a Pregnant Mother Checking Her Pregnancy (Antenatal Care) at Melak Health Center - Mandasari, Enita; Lamri, H.; Suryani, Heni (Rifa'Institute, 2023)
Introduction: In general, the maternal mortality rate in Indonesia has decreased from 390 to 305 per 100,000 live births. Health services for pregnant women must meet the minimum frequency in each trimester, namely at least once in TM 1 (0-12 weeks), at least once in TM 2 (12-24 weeks), and at least twice in TM 3 (24-40 weeks). Obejtive: This study will analyze the factors that influence pregnant women to check their pregnancy (antenatal care), with the aim of analyzing what factors are related to antenatal care at the Melak Health Center. Methods: This study used a cross sectional design. The study population was all pregnant women who visited the Melak Health Center. Result and Duscussion: Most respondents are Mature Pregnancy 21-35 years old (77.8%), Medium Education Level (68.5%), Primiparous Parity (38.9%), Not Working (59.3%), and Good Knowledge Level (74.1 %). And the results of the logistic regression test obtained age factor (0.758), education factor (2.270), parity factor (6.006), occupation factor (1.722), and knowledge factor (1.643). Conclusion: Educational factors and parity factors that influence antenatal care at the Melak Health Center. And the most dominant factor influencing antenatal care at the Melak Health Center is the parity factor